Upaya Pencegahan Stunting Di Desa Sukorejo Melalui Pemberdayaan Dan Edukasi Kepada Kader Posyandu - Estrin Handayani; Melda Handayani Saumaningrum; Nia Afifatul Handayani Ulya; Aziza Vira Handayani Arunita; Finna Sela Handayani Oktavia; Vita Handayani Fadhilah (STMIK Royal, 2023)
The high incidence of stunting is of concern to the government. Some of the causes of stunting are the lack of intake that is absorbed by the body from still in the womb until after birth, lack of access to health services, and lack of access to clean water and sanitation. Therefore, it is necessary to prevent stunting by improving diet, parenting, and sanitation. With the problem of stunting cases being still high in the Magelang Regency area and it was noted that in the Sukorejo Village area, Tegalrejo District, there were still around 17.95% of stunting cases, the Integrated Community Service team, Faculty of Health Sciences, Universitas Muhammadiyah Magelang, will conduct training for Posyandu cadres in the village. Sukorejo. The team will implement Cadre Empowerment and Education in managing Posyandu as an effort to revitalize Posyandu for specific nutrition interventions for children. The purpose of this activity is to reduce the number of stunting cases in the Sukorejo Village, Tegalrejo District, Magelang Regency.Keywords: cadre; catfish nuggets; child nutrition; stunting; posyandu. Abstrak: Pemerintah prihatin dengan banyaknya kasus stunting. Beberapa penyebab stunting sendiri adalah kurangnya nutrisi yang diserap tubuh setelah lahir di dalam kandungan, kurangnya pelayanan kesehatan, kurangnya air bersih dan sanitasi. Oleh karena itu perlu untuk mencoba mencegah penurunan dengan meningkatkan gizi, pelatihan dan kebersihan. Dikarenakan permasalahan kasus Stunting yang masih tinggi di Kabupaten Magelang, ditemukan bahwa wilayah Desa Sukorejo di Tegalrejo masih memiliki kasus Stunting sekitar 17,95 persen. maka tim Pengabdian Pada Masyarakat Terpadu Fakultas Ilmu Kesehatan Universitas Muhammadiyah Magelang, akan melaksanakan pelatihan bagi para kader Posyandu di Desa Sukorejo. Tim PPMT FIKES UNIMMA ini akan menerapkan Pemberdayaan dan Edukasi Kader di dalam mengelola Posyandu sebagai upaya merevitalisasi Posyandu untuk intervensi gizi spesifik pada anak. Tujuan dari kegiatan ini adalah mengurangi angka kasus stunting di wilayah Desa Sukorejo Kecamatan Tegalrejo Kabupaten Magelang.Kata Kunci: gizi anak; nugget lele; posyandu; stunting